Exploration of Teachers' Perceptions and Challenges in Using Artificial Intelligence in Learning - Alivia Rizky Wulan Santoso; Rafii Fathul Alim; Dewi Maharani (Journal on Smart Learning Technologies, 2026)
The rapid development of Artificial Intelligence (AI) in education has created significant opportunities to improve teaching and learning processes; however, teacher readiness and perceptions remain diverse, particularly at the elementary school level. This study aims to explore teachers' perceptions and challenges in using AI in classroom learning. The research employed a qualitative descriptive-exploratory design involving eight elementary school teachers selected through purposive sampling in Magetan Regency. Data were collected through semi-structured interviews and non-participant observation, and analyzed using thematic analysis techniques. The findings indicate that teachers generally have positive perceptions of AI, viewing it as a supportive tool to increase efficiency, creativity, and access to learning resources. However, understanding and practical use of AI are still in their infancy, with limited direct integration into classroom practice. The study also identified several challenges, including limited digital competency, lack of institutional training and support, inadequate infrastructure, and concerns about AI accuracy and student dependability. These findings suggest that while AI has strong potential to improve pedagogical practice, its effective implementation depends on improving teacher competency and providing systematic support. This study contributes to the theoretical understanding of teacher-AI interactions in primary education and highlights the need for professional development programs, policy support, and ethical guidance to ensure the responsible and effective integration of AI in education.